Geothermal gradients and heat flow in Norte Basin of Uruguay - Morales, Ethel (2020)
Progress obtained in a partial update of geothermal gradient and terrestrial heat flow values for the Norte Basin (Uruguay) are presented. It is based on results of temperature measurements carried out in deep water wells. Most of these wellshave intersected the southern part of the Guarani Aquifer System, at depths varying from 200 to 1500m. In most of the Norte Basin it is a confined aquifer capped by the flood basalts of Cretaceous age. The results indicate that temperature gradients fall in the range of 15 to 45oC/km and the thermal conductivity of basalts have a mean value of 2.2W/m/K. Analysis of temperature distributions indicate that heat transfer takes place not only by conduction but also by upflow of groundwater with velocities in the range of 10-9to 10-8m/s. The representative mean heat flow values fall in the range of 30 to 85mW/m2. Maps of spatial distributions of geothermal gradients and heat flow values have been considered as indicative of he possible existence of an anomalous geothermal zone in the central-northwestern part of the Norte Basin. There are indications that this anomalous geothermal zone extends also to the eastern parts of adjacent regions in Argentina. Theoretical values derived on the basis of spherical harmonic expansion, employed in estimating geothermal gradients and heat flow points to a zone of relatively low heat flow in the other regions of the Norte Basin.